Árbitro de emergência: - Xavier, Camila de Arruda (2022)
The thesis hereby seeks to analyze the emergency arbitrator institute, the way in which this institute presents itself in arbitrations and its importance in the arbitral procedures. In the scope of arbitration, the parties often need to have their right protected even before the Arbitral Tribunal is constituted, whether these are domestic, expedited, investment or international commercial arbitrations. This mechanism does not require judicial interference, that is, resorting to state jurisdiction in order to issue an urgency measure. In the meantime, the emergency arbitrator emerges as a way to protect one or both parties, by issuing urgency measures even before the constitution of the Arbitral Tribunal. In a global sphere, the emergency arbitrator is currently provided for in several arbitration chamber rules, which makes a deep study on this institute necessary and fundamental. In the thesis hereby, the research is limited to the 2017 Regulation of the International Chamber of Commerce (International Chamber of Commerce) – reference in international arbitration – and the relevance and applicability of the emergency arbitrator for arbitrations will be analyzed.